Cellulose nanomaterials: promising sustainable nanomaterials for application in water/wastewater treatment processes - Mohammed, Nishil; Grishkewich, Nathan; Tam, Kam Chiu (Environmental science. Nano, 2018)
In recent years, sustainable nanomaterials, such as cellulose nanocrystals (CNCs) and cellulose nanofibrils (CNFs), jointly referred to as cellulose nanomaterials (CNs), have been explored for application in water/wastewater treatment processes. Unique properties of CNs coupled with the global quest to develop low carbon footprint alternatives as aids for water treatment processes have been the driving force for the increasing interest among researchers worldwide. There are several reviews that describe the chemistry and modification of CNs; however, a comprehensive review on the potential application of CNs in water/wastewater treatment processes is scarce. Thus, this review provides a detailed overview of pristine, surface-functionalized CNs and CN-incorporated nanocomposites for applications in various water/wastewater treatment processes, such as sorption, membrane filtration, and flocculation. The latest advances and developments on other processes using CNs, such as catalytic degradation and disinfection, are also discussed. The mechanism responsible for the performance of CN-based systems in all these water treatment processes is also elucidated. The key challenges and knowledge gaps that limit the practical application of CNs in water treatment processes are examined, which offer appropriate perspectives to researchers working in this field. Schematic diagram showing the various water/wastewater treatment processes in which CN-based systems can be utilized.